2016
DOI: 10.1016/j.rpped.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades de assistência à criança com deficiência – Uso do Inventário de Avaliação Pediátrica de Incapacidade

Abstract: Social function was the area referred to as the one that needed a higher degree of assistance from the caregiver and the Pediatric Evaluation of Disability Inventory is a tool that can help identify these needs and develop a more targeted intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Em pesquisa realizada no Estado de São Paulo com crianças que faziam uso da gastrostomia, verificou-se que a maioria era do sexo masculino 8,9 , porém, há estudos que evidenciam o predomínio de crianças do sexo feminino com uso da gastrostomia 10 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em pesquisa realizada no Estado de São Paulo com crianças que faziam uso da gastrostomia, verificou-se que a maioria era do sexo masculino 8,9 , porém, há estudos que evidenciam o predomínio de crianças do sexo feminino com uso da gastrostomia 10 .…”
Section: Resultsunclassified
“…Ao analisar a escolaridade de pacientes com gastrostomia, na pesquisa com 17 crianças e adolescentes, revelou-se que grande parte desses indivíduos não frequentavam a escola 8 . Uma das justificativas para esse alto número, está no fato de que os mesmos além de dependerem de um dispositivo que possibilite a nutrição enteral pela gastrostomia, apresentam também comorbidades, como por exemplo, a neuropatia crônica, o que inviabiliza muita das vezes a sua ida a escola 8,9 .…”
Section: Resultsunclassified
“…In these studies, PEDI made it possible to identify individual disabilities contributing to the long-term monitoring of students, 13 besides, pointing out social function as the most compromised area, enabling the planning of interventions for children and their families in the research setting. 14 Analysis of the articles revealed that PEDI was used in research with children with Cerebral Palsy (CP) and occipital meningoencephalocele sequelae to analyze the benefits of aquatic physical activity 15,6 and equine therapy. 17 Using PEDI, before and after the researchers' intervention, these Studies have shown that physical activity, especially that developed in the aquatic environment, tends to improve social function, mobility, and manual skills; In addition to promoting greater independence and more effective social participation.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that visual impairment interferes with the knowledge of one's own body and its interaction with the objects and people in the environment 24 . Telles et al 25 who evaluated 181 children aged 7 to 10 years with physical or mental disabilities in the process of school inclusion, observed that children with physical disabilities had the lowest means for mobility and for self-care (caregiver´s assistance), showing that children needed more help from the caregiver in these two domains.…”
Section: Discussionmentioning
confidence: 99%